2017
DOI: 10.35699/1981-3171.2017.1593
|View full text |Cite
|
Sign up to set email alerts
|

O Lazer nas Diferentes Fases da Vida de Centenários

Abstract: RESUMO: O objetivo desse estudo é analisar o lazer nas diferentes fases da vida de centenários. Trata-se de um estudo de natureza qualitativa e teve como participantes seis centenários (102,83±1,6) e seus respectivos cuidadores. O grupo foi selecionado a partir dos critérios de inclusão: ter idade igual ou superior a cem anos comprovada por documento, ter condições cognitivas preservadas e residir nos municípios da mesorregião Grande Florianópolis (SC). O instrumento utilizado foi o Protocolo de Avaliação Mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0
12

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 17 publications
(12 reference statements)
1
0
0
12
Order By: Relevance
“…This is due to lower exposure to certain occupational risk factors, greater female concern for their own health and self-care, and frequent use of health services in search of care (JÚNIOR et al, 2019). Naman et al (2017), reinforce that this phenomenon has been following the population aging in the world, being more evident in the older age groups. When reporting this phenomenon, the authors state that older women are more likely to be widowed, which can be observed in the data of this study where they reported by 73.2% the widowed marital status.…”
Section: Resultssupporting
confidence: 58%
“…This is due to lower exposure to certain occupational risk factors, greater female concern for their own health and self-care, and frequent use of health services in search of care (JÚNIOR et al, 2019). Naman et al (2017), reinforce that this phenomenon has been following the population aging in the world, being more evident in the older age groups. When reporting this phenomenon, the authors state that older women are more likely to be widowed, which can be observed in the data of this study where they reported by 73.2% the widowed marital status.…”
Section: Resultssupporting
confidence: 58%
“…Por outro lado, foi identificado, também, o aumento de atividades cognitivas/sedentárias. Desta forma, é oportuno dissertar acerca da importância de oportunizar diferentes práticas às pessoas com idade mais avançada, com o intuito de manter o desenvolvimento saudável, ao longo de todo o processo de vida (NAMAN et al, 2017). Ampliar as possibilidades de vivências para além de atividades passivas e rotineiras (AVITAL, 2017), representa um desafio para os grupos de convivência e para os projetos de extensão universitária, os quais atuam com o público idoso.…”
Section: Discussionunclassified
“…Na fase adulta: trabalho, viagens, passeios, atividades manuais. Durante a velhice: viagens, trabalho, assistir televisão e por fim, na fase atual: assistir televisão, religiosidade e passeios (n = 3) (NAMAN et al, 2017).…”
Section: Alves 2018unclassified